2017
DOI: 10.1039/c7ta03340k
|View full text |Cite
|
Sign up to set email alerts
|

K-doped Sr2Fe1.5Mo0.5O6−δ predicted as a bifunctional catalyst for air electrodes in proton-conducting solid oxide electrochemical cells

Abstract: Electronic structure features and surface reconstruction make K-doped Sr2Fe1.5Mo0.5O6−δ a promising electrode for both oxygen reduction and evolution reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…A volcano-type plot along the e g electron number was originally proposed by Suntivich et al, 17 and is widely accepted at present. 21,22,[39][40][41][42][43][44][45][46][47][48] Figure 4a shows η versus e g electron number for the perovskite oxides, where the e g electron numbers were estimated from the most likely electron configurations (Table S3) Indeed, these average values apparently followed a gradient volcano-like shape (dashed curve in Figure 4a). However, compared with the previous report, 17 it does not efficiently serve to describe OER activity because of wide dispersion of data points (see error bars in Figure 4a).…”
Section: Xrd Patterns Inmentioning
confidence: 99%
“…A volcano-type plot along the e g electron number was originally proposed by Suntivich et al, 17 and is widely accepted at present. 21,22,[39][40][41][42][43][44][45][46][47][48] Figure 4a shows η versus e g electron number for the perovskite oxides, where the e g electron numbers were estimated from the most likely electron configurations (Table S3) Indeed, these average values apparently followed a gradient volcano-like shape (dashed curve in Figure 4a). However, compared with the previous report, 17 it does not efficiently serve to describe OER activity because of wide dispersion of data points (see error bars in Figure 4a).…”
Section: Xrd Patterns Inmentioning
confidence: 99%
“…Mo‐based double perovskites have attracted more and more attention due to their good mixed ionic‐electronic conductivity, mechanical stability and acceptable expansion behavior with various temperatures and pO 2 values . Moreover, it was found that these oxides (e.g., Sr 2 Fe 1.5 Mo 0.5 O 6−δ ) may have high bulk proton transport, which was favorable for proton‐conducting SOCs. In Ding et al's work, the BFM electrodes were prepared by solid state reaction (SSR) and Pechini methods .…”
Section: Functional Materials Of Proton‐conducting Socsmentioning
confidence: 99%
“…The cathodic CO 2 reduction reaction (CO 2 RR) is usually expressed in the Kröger-Vink notation as where e – is an excess free electron in n-type conductor, V O •• is the oxygen vacancy provided by the electrode and/or electrolyte materials, and O O × is the lattice oxygen atom. Based on the oxygen reduction reaction mechanism proposed by Muñoz-García and Pavone, the CO 2 RR processes might consist of elementary steps as follows, So, the cathode must have high catalytic activity and electronic and ionic conductivities.…”
Section: Introductionmentioning
confidence: 99%